Inkjet-printed alloy-like cross-linked hole-transport layer for high-performance solution-processed green phosphorescent OLEDs. Issue 37 (23rd August 2021) - Pan, Yichen; Liu, Hongli; Wang, Shirong; Han, Xinjun; Li, Xianggao
Abstract : Green phosphorescent OLEDs based on non-bank inkjet-printed alloy-like HTLs exhibit a superior luminescence performance. Abstract : The coffee-ring effect and material aggregation are main obstacles to obtaining high-performance small-molecule hole-transport layers by non-bank inkjet printing for organic light-emitting diodes (OLEDs). In this paper, a binary solvent ink system of cyclohexane-dipropylene glycol methyl ether (CYC–DGME) was constructed for the cross-linkable hole-transport material N, N ′-di- p -tolyl- N, N ′-bis(4-vinylphenyl)-[1, 1′-biphenyl]-4, 4′-diamine (V- p -TPD). The coffee-ring effect during film formation was eliminated by adjusting the solvent ratio and printing conditions. Furthermore, N 2, N 2, N 7, N 7 -tetrakis(4-(3, 6-di- tert -butyl-9 H -carbazol-9-yl)-phenyl)-9, 9-dimethyl-9 H -fluoren-2, 7-diamine ( p -BCz-F) was used as the auxiliary hole-transport component. With V- p -TPD/ p -BCz-F = 8 : 2 and CYC/DGME = 7 : 3, non-bank inkjet printing and thermal cross-linking produced an alloy-like hole-transport layer film with a low surface roughness (RMS = 1.23 nm) and excellent resistance to solvents. The target green phosphorescent OLEDs were qualified with an enhanced maximum current efficiency, external quantum efficiency and lowered turn-on voltage of 55.47 cd A −1, 15.44% and 3.18 V, respectively, which represents a state-of-the-art record among OLEDs based on inkjet-printed HTLs. This result provides an effective and unique approach for the facile preparation of highly efficient OLED display devices by inkjet printing.